KONSEP PENGELOLAAN PAJAK YANG ADIL PERSPEKTIF IBNU KHALDUN - Jirhanuddin Jirhanuddin (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2016)
This research is motivated by the thought of Ibn Khaldun regarding taxes. According to Ibn Khaldun if the tax is too low, can not lead a government function, if the tax is too high, fiscal pressure becomes too strong, so the profits traders and producers declined and there goes their incentive to work.The purpose of this study was to learn the concept of a fair tax management perspective by Ibn Khaldun in order to build a modern economy that is equitable and to find out how the tax relevance according to Ibn Khaldun with today's modern economy.This research method used literature study (library research) with descriptive qualitative type of research. The data source consisted of Muqaddimah books as primary sources, work or theory that discussed of primary materials as secondary materials and the complement of primary and secondary materials as tertiary material. The approach in this study was a historical approach and philosophic. Data collection method used existing literature and data analysis used content analysis and the hermeneutic.The study concluded that the concept of fair tax perspective of Ibn Khaldun is a tax that is withdrawn from the taxpayer in accordance with the ability of taxpayers to pay and the money tax collection should be used properly and fairly as possible, according to Ibn Khaldun when the tax burden lighter, people have an incentive to try to be more active. Therefore, the business world become more advanced, leading to greater satisfaction among the people, because of the low tax burden while tax revenue will also increase, judging from the overall resources of land tax, the thought of Ibn Khaldun regarding taxes is very relevant to be applied to the condition of modern economy of this time where the economic situation is less stable, the situation of society more complicated, the prices of expensive life needs make people’s life difficult.